The lexical field of the substantives of "gift" in ancient Hebrew - Zanella, Francesco (Studia Semitica Neerlandica, 2010)
Contents; Acknowledgements; Foreword; Abbreviations; Methodological Framework; 1. Biblical Hebrew or Ancient HebrewBetween Language and Corpus; 2. Componential Analysis of Meaning; 2.1 Why Componential Analysis of Meaning; 2.2 Theoretical Framework; 2.3 Research Procedures of Componential Analysis; 3. Between Synchrony and Diachrony: Componential Analysis and the Issue of Linguistic Change; 4 Componential Analysis as a Heuristic Tool for Cognitive SemanticsSome Methodological Considerations; Part One Distributional and Syntagmatic Analysis; Lexeme 1: אשֶכְׁרָּ.